Resin composition for forming phase separation structure, and method for producing structure including phase separation structure

A resin composition with a specific L0 ratio of 0.70 to 1.20 for block copolymers A and B improves process margin and enables defect-free pattern formation across multiple pitches, addressing the limitations of existing methods in forming phase separation structures.

JP2025017056APending Publication Date: 2025-02-05TOKYO OHKA KOGYO CO LTD

Patent Information

Application Number
JP2023119926
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

Existing methods for forming phase separation structures using block copolymers require individual preparation for each pitch, limiting the applicability and process margin, and there is a need for a resin composition that can form patterns across multiple pitches without defects.

Method used

A resin composition containing block copolymers A and B, with a specific L0 ratio of 0.70 to 1.20, is used to form phase separation structures, allowing for improved process margin and pattern formation across multiple pitches.

Benefits of technology

The resin composition enhances the process margin and enables defect-free pattern formation across various pitches, expanding the applicability of phase separation structures in nanoscale manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017056000012
    Figure 2025017056000012
  • Figure 2025017056000013
    Figure 2025017056000013
  • Figure 2025017056000001
    Figure 2025017056000001
Patent Text Reader

Abstract

To provide a resin composition for forming a phase separation structure that achieves improved process margin.SOLUTION: A resin composition for forming a phase separation structure contains a predetermined block copolymer A and block copolymer B. The ratio of L0 of the block copolymer B (L0B) to L0 of the block copolymer A (L0A), (L0B / L0A), is 0.70-1.20.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for forming a phase-separated structure, and a method for producing a structure containing a phase-separated structure. [Background technology]

[0002] In recent years, with the further miniaturization of large-scale integrated circuits (LSIs), there is a demand for technology to process more delicate structures. In response to such demands, technology is being developed to form finer patterns by utilizing a phase-separated structure formed by the self-organization of a block copolymer in which mutually incompatible blocks are bonded together (see, for example, Patent Document 1).

[0003] The block copolymer is separated (phase separated) in a microscopic region due to repulsion between mutually incompatible blocks, and forms a structure having a regular periodic structure by heat treatment, etc. Specific examples of this periodic structure include cylinders (columnar), lamellae (plates), spheres, etc.

[0004] In order to utilize the phase separation structure of a block copolymer, it is essential to form the self-organized nanostructure formed by microphase separation only in a specific region and to align it in a desired direction. To achieve this position control and orientation control, processes such as graphoepitaxy, which controls the phase separation pattern by a guide pattern, and chemical epitaxy, which controls the phase separation pattern by differences in the chemical state of the substrate, have been proposed (see, for example, Non-Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-36491 A [Non-patent literature]

[0006] [Non-Patent Document 1] Proc. SPIE 7637, Alternative Lithographic Technologies II, 76370G (1 April 2010) Summary of the Invention [Problem to be solved by the invention]

[0007] In the method of forming a pattern using a phase-separated structure formed by the self-organization of a block copolymer, it is necessary to prepare a block copolymer having a structure period (L0) that matches one pitch. Therefore, for designs with multiple pitches, it is necessary to prepare individual block copolymers. If one phase-separated structure-forming resin composition could be used for a plurality of pitches, the scope of application of the above-mentioned pattern formation method would be greatly expanded. Therefore, in the above-mentioned pattern formation method, a phase-separated structure-forming resin composition with a large process margin is required so that a pattern with a plurality of pitches can be formed without causing defects in the pattern.

[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a resin composition for forming a phase-separated structure that can improve process margins, and a method for producing a structure including a phase-separated structure using the resin composition for forming a phase-separated structure. [Means for solving the problem]

[0009] In order to solve the above problems, the present inventors have conducted extensive research and have discovered that a polymerizable composition containing a specific block copolymer A and a specific block copolymer B, in which L0 of the block copolymer A (L0 A ) for block copolymer B (L0 B ) ratio (L0 B / L0 A The inventors have found that the above problems can be solved if the ratio of the surface area of ​​the resin to the surface area of ​​the resin is 0.70 to 1.20, and have completed the present invention. Specifically, the present invention provides the following.

[0010] [1] A resin composition for forming a phase-separated structure, comprising a block copolymer A and a block copolymer B, The block copolymer A is a block copolymer in which a 1a block, a 2a block, and a 3a block are bonded together, The block copolymer B is a block copolymer in which a 1b block and a 2b block are bonded together, a structural unit of a polymer constituting the 1a block, a structural unit of a polymer constituting the 3a block, and a structural unit of a polymer constituting the 1b block have the same structure, a structural unit of the polymer constituting the 2a block and a structural unit of the polymer constituting the 2b block have the same structure, L0 of the block copolymer A (L0 A ) to L0 (L0 B ) ratio (L0 B / L0 A ) is 0.70 to 1.20.

[0011] [2] The resin composition for forming a phase-separated structure according to [1], wherein a ratio (A / B) of a mass of the block copolymer A to a mass of the block copolymer B is 99 / 1 to 50 / 50.

[0012] [3] the 1a block, the 3a block, and the 1b block are each composed of a polymer having a structural unit containing an aromatic group, The resin composition for forming a phase-separated structure according to [1] or [2], wherein the 2a block and the 2b block are made of a polymer having a structural unit derived from an (α-substituted) acrylic acid ester.

[0013] [4] forming a layer of a neutralized film on a support; applying the resin composition for forming a phase-separated structure according to any one of [1] to [3] onto the layer made of the neutralized film to form a layer containing the block copolymer A and the block copolymer B; and causing phase separation between a layer containing the block copolymer A and a layer containing the block copolymer B. Effect of the Invention

[0014] According to the present invention, it is possible to provide a resin composition for forming a phase-separated structure, which can improve the process margin, and a method for producing a structure including a phase-separated structure using the resin composition for forming a phase-separated structure. [Brief description of the drawings]

[0015] [Figure 1] 1A to 1C are schematic process diagrams illustrating an embodiment of a method for producing a structure including a phase-separated structure. [Diagram 2] FIG. 13 is a diagram illustrating an example embodiment of an optional step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The following describes in detail the embodiments of the present invention. However, the present invention is not limited to the following embodiments and can be implemented with appropriate modifications within the scope of the object of the present invention.

[0017] In this specification, the term "aliphatic" is a relative concept to aromatic, and refers to a group, compound, etc. that does not have aromaticity. The term "alkyl group" refers to a linear or branched monovalent saturated hydrocarbon group, unless otherwise specified. The same applies to the alkyl group in an alkoxy group. The term "cycloalkyl group" means, unless otherwise specified, a monocyclic saturated cyclic hydrocarbon group. The term "alkylene group" means, unless otherwise specified, a linear or branched divalent saturated hydrocarbon group. The term "halogenated alkyl group" refers to an alkyl group in which some or all of the hydrogen atoms have been replaced with halogen atoms, such as fluorine, chlorine, bromine, and iodine atoms. The term "fluorinated alkyl group" or "fluorinated alkylene group" refers to an alkyl or alkylene group in which some or all of the hydrogen atoms have been substituted with fluorine atoms. The term "structural unit" refers to a monomer unit that constitutes a polymeric compound (resin, polymer, copolymer). The term "derived structural unit" refers to a structural unit formed by cleavage of an ethylenic double bond or a cyclic ether. The phrase "optionally has a substituent" includes both the case where a hydrogen atom (-H) is replaced with a monovalent group and the case where a methylene group (-CH2-) is replaced with a divalent group. "Exposure" generally refers to exposure to radiation. Unless otherwise specified, the "α-position (carbon atom at the α-position)" refers to the carbon atom to which the side chain of the block copolymer is bonded. The "α-position carbon atom" of a methyl methacrylate unit refers to the carbon atom to which the carbonyl group of methacrylic acid is bonded. The "α-position carbon atom" of a styrene unit refers to the carbon atom to which a benzene ring is bonded. "Number average molecular weight" (Mn) means, unless otherwise specified, the number average molecular weight measured by size exclusion chromatography relative to standard polystyrene. "Weight average molecular weight" (Mw) means the weight average molecular weight measured by size exclusion chromatography in terms of standard polystyrene unless otherwise specified. The Mn or Mw value is expressed in units (gmol -1 ) the value represents the molar mass. In this specification, some structures represented by chemical formulas may have asymmetric carbons, and enantiomers or diastereomers may exist. In such cases, one formula represents all the isomers. These isomers may be used alone or as a mixture.

[0018] In this specification, the "period of the structure" means the period of the phase structure observed when the phase-separated structure is formed, and refers to the sum of the lengths of each phase that is incompatible with each other. When the phase-separated structure forms a cylindrical structure perpendicular to the substrate surface, the period (L0) of the structure is the center-to-center distance (pitch) between two adjacent cylindrical structures.

[0019] It is known that the period of the structure (L0) is determined by the degree of polymerization N and the inherent polymerization properties such as the Flory-Huggins interaction parameter χ. In other words, the larger the product of χ and N, χ·N, the greater the mutual repulsion between different blocks in the block copolymer. Therefore, when χ·N>10.5 (hereinafter referred to as the "strength separation limit"), the repulsion between different types of blocks in the block copolymer is large, and phase separation is more likely to occur. At the strength separation limit, the period of the structure is approximately N 2 / 3 χ 1 / 6 Thus, the relationship of the following formula (cy) is established. In other words, the period of the structure is proportional to the degree of polymerization N, which correlates with the molecular weight and the molecular weight ratio between different blocks.

[0020] L0 ∝ a N 2 / 3 χ 1 / 6 (cy) [In the formula, L0 represents the period of the structure, a represents a parameter indicating the size of the monomer, N represents the degree of polymerization, and χ represents an interaction parameter, and the larger this value is, the higher the phase separation performance is.]

[0021] Therefore, the period (L0) of the structure can be adjusted by adjusting the composition and total molecular weight of the block copolymer.

[0022] ≪Resin composition for forming phase-separated structure≫ The resin composition for forming a phase-separated structure contains block copolymer A and block copolymer B. Block copolymer A is a block copolymer in which a 1a block, a 2a block, and a 3a block are bonded together, and block copolymer B is a block copolymer in which a 1b block and a 2b block are bonded together. The structural units of the polymer constituting the 1a block, the structural units of the polymer constituting the 3a block, and the structural units of the polymer constituting the 1b block have the same structure, and the structural units of the polymer constituting the 2a block and the structural units of the polymer constituting the 2b block have the same structure. L0 (L0 A ) for block copolymer B (L0 B ) ratio (L0 B / L0 A ) is 0.70 to 1.20. By using such a resin composition for forming a phase-separated structure, the process margin can be improved.

[0023] The reason why such an effect is obtained is unclear, but is speculated as follows. A triblock copolymer (ABA) in which an A block, a B block, and an A block are bonded has two bonding points connecting different block chains. Therefore, ABA molecules show a bridge type molecular form in which two bonding points are located on different interfaces in the microdomain, and a loop type molecular form in which two bonding points are located on the same interface. When ABA and a diblock copolymer (AB) have the same L0, one ABA molecule has the length of two AB molecules, so the number average molecular weight (Mn) of ABA is twice that of AB. Therefore, in ABA, the margin on the guide pitch side larger than L0 increases. However, if Mn is large, the thermal kinetics during annealing decreases, and phase separation does not proceed sufficiently in the limited process time, which tends to increase defects. In contrast, if AB having a predetermined L0 ratio is added in addition to ABA, the thermal mobility is maintained, making it easier to suppress defects even in a limited process time and improving the process margin.

[0024] <Block copolymer A> Block copolymer A is a block copolymer in which a 1a block, a 2a block, and a 3a block are bonded together. The structural units of the polymer constituting the 1a block and the structural units of the polymer constituting the 3a block have the same structure.

[0025] The block copolymer A is preferably a block copolymer in which a 1a block, a 2a block, and a 3a block are bonded in this order. Block copolymer A is preferably a triblock copolymer having no blocks other than the 1a block, the 2a block, and the 3a block.

[0026] Examples of the polymer constituting the 1a block and the 3a block include a polymer having a structural unit containing an aromatic group, a polymer having a structural unit derived from an alkylene oxide, a polymer having a structural unit containing a cage-type silsesquioxane structure, etc. Among these, a polymer having a structural unit containing an aromatic group is preferred.

[0027] Examples of the polymer constituting the 2a block include a polymer having a structural unit derived from (α-substituted) acrylic acid, a polymer having a structural unit derived from (α-substituted) acrylic ester, a polymer having a structural unit of siloxane or a derivative thereof, etc. Among these, a polymer having a structural unit derived from (α-substituted) acrylic ester is preferred.

[0028] Examples of the block copolymer A include a block copolymer obtained by combining a plurality of blocks having structural units containing an aromatic group with a block having structural units derived from an (α-substituted) acrylic acid ester; a block copolymer obtained by combining a plurality of blocks having structural units containing an aromatic group with a block having structural units derived from an (α-substituted) acrylic acid; a block copolymer obtained by combining a plurality of blocks having structural units containing an aromatic group with a block having structural units of siloxane or a derivative thereof; a block copolymer obtained by combining a plurality of blocks having structural units derived from an alkylene oxide with a block having structural units derived from an (α-substituted) acrylic acid ester; block copolymers obtained by combining multiple blocks having structural units derived from an oxide with a block having structural units derived from (α-substituted) acrylic acid; block copolymers obtained by combining multiple blocks having structural units containing a cage-type silsesquioxane structure with a block having structural units derived from an (α-substituted) acrylic acid ester; block copolymers obtained by combining multiple blocks having structural units containing a cage-type silsesquioxane structure with a block having structural units derived from (α-substituted) acrylic acid; block copolymers obtained by combining multiple blocks having structural units containing a cage-type silsesquioxane structure with a block having structural units of siloxane or a derivative thereof.

[0029] [Structural units containing aromatic groups] The aromatic group in the aromatic group-containing structural unit is a group that has at least one aromatic ring. The aromatic ring is not particularly limited as long as it is a cyclic conjugated system having 4n+2 π electrons, and may be an aromatic hydrocarbon ring or an aromatic heterocycle. Among these, an aromatic hydrocarbon ring is preferred. Specific examples of the aromatic group in the aromatic group-containing structural unit include a phenyl group, a naphthyl group, an anthracenyl group, a biphenylyl group, and a pyridinyl group.

[0030] As the structural unit containing an aromatic group, a structural unit derived from styrene, a styrene derivative, 1-vinylnaphthalene, 4-vinylbiphenyl, 9-vinylanthracene, or vinylpyridine is preferable, and a structural unit derived from styrene or a styrene derivative is more preferable. The term "styrene derivative" encompasses compounds in which the hydrogen atom bonded to the α-position of styrene is substituted with a substituent such as an alkyl group having 1 to 10 carbon atoms, and compounds in which the hydrogen atom of the phenyl group of styrene is substituted with a substituent such as an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a hydroxy group, a nitro group, a halogen atom, or an acetoxy group. Specific examples of the styrene derivative include α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-tert-butylstyrene, 4-n-octylstyrene, 2,4,6-trimethylstyrene, 4-methoxystyrene, 4-tert-butoxystyrene, 4-hydroxystyrene, 4-nitrostyrene, 3-nitrostyrene, 4-chlorostyrene, 4-fluorostyrene, 4-acetoxystyrene, and 4-chloromethylstyrene. Examples of the structural unit containing an aromatic group include the structural unit represented by formula (u1) described below.

[0031] [Structural units derived from (α-substituted) acrylic esters] In this specification, the term "(α-substituted) acrylic ester" includes acrylic esters and acrylic acid derivatives in which the hydrogen atom bonded to the carbon atom at the α-position in the acrylic ester is substituted with a substituent. Examples of the substituent in the (α-substituted) acrylic ester include an alkyl group having 1 to 5 carbon atoms and a halogenated alkyl group having 1 to 5 carbon atoms. Among these, an alkyl group having 1 to 5 carbon atoms is preferred, and a methyl group is more preferred.

[0032] The (α-substituted) acrylic acid ester is preferably an (α-substituted) alkyl acrylate. The number of carbon atoms in the alkyl group in the (α-substituted) alkyl acrylate is preferably 1 to 10, and more preferably 1 to 5. Specific examples of the (α-substituted) acrylic acid ester include acrylic acid esters such as methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, octyl acrylate, nonyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, benzyl acrylate, anthracene acrylate, glycidyl acrylate, 3,4-epoxycyclohexylmethane acrylate, and propyltrimethoxysilane acrylate; and methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, octyl methacrylate, nonyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, benzyl methacrylate, anthracene methacrylate, glycidyl methacrylate, 3,4-epoxycyclohexylmethane methacrylate, and propyltrimethoxysilane methacrylate.

[0033] Of the above, the (α-substituted) acrylic esters are preferably alkyl acrylates and alkyl methacrylates, more preferably methyl acrylate, ethyl acrylate, tert-butyl acrylate, methyl methacrylate, ethyl methacrylate, and tert-butyl methacrylate, and even more preferably methyl methacrylate. Examples of the structural unit derived from an (α-substituted) acrylic ester include the structural unit represented by the formula (u2) described below.

[0034] [Structural units derived from (α-substituted) acrylic acid] In this specification, the term "(α-substituted) acrylic acid" includes acrylic acid and acrylic acid derivatives in which the hydrogen atom bonded to the carbon atom at the α-position in acrylic acid is substituted with a substituent.

[0035] Specific examples of the (α-substituted) acrylic acid include acrylic acid and methacrylic acid.

[0036] [Structural unit of siloxane or its derivative] Specific examples of siloxane or a derivative thereof include dimethylpolysiloxane, diethylpolysiloxane, diphenylpolysiloxane, and methylphenylpolysiloxane.

[0037] [Structural units derived from alkylene oxide] Specific examples of the alkylene oxide include ethylene oxide, propylene oxide, isopropylene oxide, and butylene oxide.

[0038] [Structural units containing cage-type silsesquioxane structure] Examples of the structural unit containing a cage silsesquioxane (POSS) structure include a structural unit represented by the following general formula (a0-1).

[0039] [ka] [In the formula, R represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a halogenated alkyl group having 1 to 5 carbon atoms. 0 R represents a divalent organic group which may have a substituent. 0 represents a monovalent organic group which may have a substituent, and a plurality of R 0 may be the same or different. * indicates a bond.]

[0040] In the formula (a0-1), the alkyl group having 1 to 5 carbon atoms represented by R is preferably a linear or branched alkyl group having 1 to 5 carbon atoms, and specific examples thereof include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, a pentyl group, an isopentyl group, and a neopentyl group. The halogenated alkyl group having 1 to 5 carbon atoms is a group in which some or all of the hydrogen atoms of the alkyl group having 1 to 5 carbon atoms are substituted with halogen atoms. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, and a fluorine atom is particularly preferred. R is preferably a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a fluorinated alkyl group having 1 to 5 carbon atoms, and from the viewpoint of industrial availability, a hydrogen atom or a methyl group is most preferable.

[0041] In the formula (a0-1), R 0 The number of carbon atoms in the monovalent organic group as is preferably 1 to 20, more preferably 1 to 10, and further preferably 1 to 8. However, this number of carbon atoms does not include the number of carbon atoms in the substituents described below. R 0 The monovalent organic group may be an aliphatic hydrocarbon group, an aromatic group, or a combination of an aliphatic hydrocarbon group and an aromatic group. Among them, an aliphatic hydrocarbon group is preferred, a monovalent aliphatic saturated hydrocarbon group is more preferred, and an alkyl group is even more preferred. The alkyl group may be a straight-chain or branched-chain alkyl group. The number of carbon atoms of the linear alkyl group is preferably 1 to 8, more preferably 1 to 5, and even more preferably 1 to 3. Specific examples of the linear alkyl group include a methyl group, an ethyl group, an n-propyl group, an n-butyl group, and an n-pentyl group. Among these, a methyl group, an ethyl group, and an n-propyl group are preferred, a methyl group and an ethyl group are more preferred, and an ethyl group is even more preferred. The number of carbon atoms of the branched alkyl group is preferably 3 to 5. Specific examples of the branched alkyl group include an isopropyl group, an isobutyl group, a tert-butyl group, an isopentyl group, and a neopentyl group. Of these, an isopropyl group, an isobutyl group, and a tert-butyl group are preferred. R 0 The monovalent organic group as may be a saturated aliphatic cyclic hydrocarbon group (a group in which one hydrogen atom has been removed from a saturated aliphatic cyclic hydrocarbon), a group in which the saturated aliphatic cyclic hydrocarbon group is bonded to the end of the aforementioned chain-like alkyl group, or a group in which the saturated aliphatic cyclic hydrocarbon group is present in the middle of the aforementioned chain-like alkyl group, or the like. The saturated aliphatic cyclic hydrocarbon group may be a monocyclic group (cycloalkyl group) or a polycyclic group. The number of carbon atoms in the cycloalkyl group is preferably 3 to 8, and more preferably 4 to 6. The polycyclic group is preferably a group in which one hydrogen atom has been removed from a polycycloalkane having 7 to 12 carbon atoms. Specific examples of the polycycloalkane include adamantane, norbornane, isobornane, tricyclodecane, and tetracyclododecane.

[0042] The chain alkyl group may have a substituent, such as a fluorine atom, a fluorinated alkyl group having 1 to 5 carbon atoms and substituted with a fluorine atom, or an oxygen atom (=O). The saturated aliphatic cyclic hydrocarbon group may have a substituent, such as an alkyl group having 1 to 5 carbon atoms, a fluorine atom, a fluorinated alkyl group having 1 to 5 carbon atoms, or an oxygen atom (=O).

[0043] R 0 When the monovalent organic group as may be an aromatic group-containing group, the aromatic group-containing group is a monovalent group having at least one aromatic ring. The aromatic ring contained in the aromatic group-containing group is not particularly limited as long as it is a cyclic group having a cyclic conjugated system with 4n+2 π electrons, and may be monocyclic or polycyclic. The number of carbon atoms in the aromatic ring is preferably 5 to 30, more preferably 5 to 20, further preferably 6 to 15, and particularly preferably 6 to 12. However, the number of carbon atoms does not include the number of carbon atoms in the substituent described below. Specific examples of the aromatic ring include aromatic hydrocarbon rings such as a benzene ring, a naphthalene ring, an anthracene ring, and a phenanthrene ring; and aromatic heterocycles in which a part of the carbon atoms constituting the aromatic hydrocarbon ring is replaced with a heteroatom. Examples of the heteroatom in the aromatic heterocycle include an oxygen atom, a sulfur atom, and a nitrogen atom. Specific examples of the aromatic heterocycle include a pyridine ring and a thiophene ring. Specific examples of the aromatic group include groups in which one hydrogen atom has been removed from the aromatic hydrocarbon ring or aromatic heterocycle (aryl groups or heteroaryl groups); and groups in which one hydrogen atom has been removed from an aromatic compound containing two or more aromatic rings (e.g., biphenyl, fluorene, etc.). The aromatic group-containing group may be a group in which one of the hydrogen atoms of the aromatic hydrocarbon ring or aromatic heterocycle is substituted with an alkylene group (for example, an arylalkyl group such as a benzyl group, a phenethyl group, a 1-naphthylmethyl group, a 2-naphthylmethyl group, a 1-naphthylethyl group, or a 2-naphthylethyl group). The alkylene group bonded to the aryl group or heteroaryl group preferably has 1 to 4 carbon atoms, more preferably 1 or 2 carbon atoms, and particularly preferably 1 carbon atom. The aromatic group may or may not have a substituent. Examples of the substituent include an alkyl group having 1 to 5 carbon atoms, a fluorine atom, a fluorinated alkyl group having 1 to 5 carbon atoms and substituted with a fluorine atom, and an oxygen atom (=O).

[0044] In the formula (a0-1), V 0 The divalent organic group in may be an aliphatic hydrocarbon group or an aromatic group-containing group that contains an aromatic ring. V 0 The aliphatic hydrocarbon group as the divalent organic group in may be saturated or unsaturated, and is usually preferably saturated. More specifically, the aliphatic hydrocarbon group may be a straight-chain or branched-chain aliphatic hydrocarbon group, or an aliphatic hydrocarbon group containing a ring in the structure.

[0045] The linear or branched aliphatic hydrocarbon group preferably has 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms, further preferably 1 to 4 carbon atoms, and most preferably 1 to 3 carbon atoms. The linear aliphatic hydrocarbon group is preferably a linear alkylene group, specifically, methylene group [-CH2-], ethylene group [-(CH2)2-], trimethylene group [-(CH2)3-], tetramethylene group [-(CH2)4-], pentamethylene group [-(CH2)5-], etc. The branched aliphatic hydrocarbon group is preferably a branched alkylene group.Specific examples of the branched alkylene group include alkyl methylene groups such as -CH(CH3)-, -CH(CH2CH3)-, -C(CH3)2-, -C(CH3)(CH2CH3)-, -C(CH3)(CH2CH2CH3)-, and -C(CH2CH3)2-; alkyl ethylene groups such as -CH(CH3)CH2-, -CH(CH3)CH(CH3)-, -C(CH3)2CH2-, -CH(CH2CH3)CH2-, and -C(CH2CH3)2-CH2-; alkyl trimethylene groups such as -CH(CH3)CH2CH2-, and -CH2CH(CH3)CH2-; and alkyl tetramethylene groups such as -CH(CH3)CH2CH2CH2-, and -CH2CH(CH3)CH2CH2-. The alkyl group in the alkylalkylene group is preferably a linear alkyl group having 1 to 5 carbon atoms.

[0046] Examples of the aliphatic hydrocarbon group containing a ring in the structure include a divalent alicyclic hydrocarbon group (a group in which two hydrogen atoms have been removed from an aliphatic hydrocarbon ring), a group in which an alicyclic hydrocarbon group is bonded to the end of a linear or branched aliphatic hydrocarbon group, a group in which the alicyclic hydrocarbon group is present in the middle of a linear or branched aliphatic hydrocarbon group, etc. Examples of the linear or branched aliphatic hydrocarbon group include the same groups as described above. The alicyclic hydrocarbon group preferably has 3 to 20 carbon atoms, and more preferably has 3 to 12 carbon atoms. The alicyclic hydrocarbon group may be a polycyclic group or a monocyclic group. The monocyclic alicyclic hydrocarbon group is preferably a group in which two hydrogen atoms are removed from a monocycloalkane. The monocycloalkane is preferably a monocycloalkane having 3 to 6 carbon atoms, specifically, cyclopentane, cyclohexane, etc. The polycyclic alicyclic hydrocarbon group is preferably a group in which two hydrogen atoms have been removed from a polycycloalkane, and the polycycloalkane is preferably a polycycloalkane having 7 to 12 carbon atoms, specific examples of which include adamantane, norbornane, isobornane, tricyclodecane, and tetracyclododecane.

[0047] V 0 The aromatic group-containing group as represented by the formula (I) is a divalent group having an aromatic ring. The aromatic ring is not particularly limited as long as it is a cyclic group having a cyclic conjugated system with 4n+2 π electrons, and may be monocyclic or polycyclic. The number of carbon atoms in the aromatic ring is preferably 5 to 30, more preferably 5 to 20, further preferably 6 to 15, and particularly preferably 6 to 12. However, the number of carbon atoms does not include the number of carbon atoms in the substituent described below. Specific examples of the aromatic ring include aromatic hydrocarbon rings such as a benzene ring, a naphthalene ring, an anthracene ring, and a phenanthrene ring; and aromatic heterocycles in which a part of the carbon atoms constituting the aromatic hydrocarbon ring is replaced with a heteroatom. Examples of the heteroatom in the aromatic heterocycle include an oxygen atom, a sulfur atom, and a nitrogen atom. Specific examples of the aromatic heterocycle include a pyridine ring and a thiophene ring. Specific examples of the aromatic group-containing group include groups in which two hydrogen atoms have been removed from the aromatic hydrocarbon ring or aromatic heterocycle (arylene groups or heteroarylene groups); and groups in which two hydrogen atoms have been removed from an aromatic compound containing two or more aromatic rings (e.g., biphenyl, fluorene, etc.). V 0The aromatic group-containing group as the aromatic group may be a group in which one hydrogen atom of a group (aryl group or heteroaryl group) obtained by removing one hydrogen atom from the aromatic hydrocarbon ring or aromatic heterocycle is substituted with an alkylene group (for example, a group in which one hydrogen atom has been further removed from the aryl group of an arylalkyl group such as a benzyl group, a phenethyl group, a 1-naphthylmethyl group, a 2-naphthylmethyl group, a 1-naphthylethyl group, or a 2-naphthylethyl group). The alkylene group bonded to the aryl group or heteroaryl group preferably has 1 to 4 carbon atoms, more preferably 1 or 2 carbon atoms, and particularly preferably 1 carbon atom.

[0048] Specific examples of the structural unit represented by the formula (a0-1) are shown below. α represents a hydrogen atom, a methyl group, or a trifluoromethyl group.

[0049] [ka]

[0050] More specifically, examples of the block copolymer A include a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from methyl acrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from ethyl acrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from tert-butyl acrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from methyl methacrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from ethyl methacrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from tert-butyl methacrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from tert-butyl methacrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from tert-butyl methacrylate;

[0051] Of the above, it is preferred that the block copolymer A has the 1a block and the 3a block each composed of a polymer having a structural unit containing an aromatic group, and the 2a block composed of a polymer having a structural unit derived from an (α-substituted) acrylic acid ester. That is, a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from methyl acrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from ethyl acrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from tert-butyl acrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from methyl methacrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from ethyl methacrylate; a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from tert-butyl methacrylate is preferred, and a block copolymer in which a plurality of blocks having structural units derived from styrene are bonded to a block having structural units derived from methyl methacrylate is more preferred.

[0052] The block copolymer A is preferably a block copolymer in which the 1a block and the 3a block are composed of a polymer having a constitutional unit represented by the following formula (u1), and the 2a block is composed of a polymer having a constitutional unit represented by the following formula (u2). The block copolymer A may further be a block copolymer in which the main chain terminal on the 2a block side has a terminal structure represented by the following formula (e1).

[0053] [ka] [In the formula, R 1 is a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a halogenated alkyl group having 1 to 5 carbon atoms. 01 is an aromatic group.

[0054] [ka] [In the formula, R 2 is a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a halogenated alkyl group having 1 to 5 carbon atoms. 01 is an alkyl group having 1 to 10 carbon atoms.

[0055] [ka] [In the formula, R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a halogenated alkyl group having 1 to 5 carbon atoms. 01 is an alkyl group having 1 to 10 carbon atoms. 01 is an aromatic group. 01 is a divalent linking group.

[0056] (Structural unit represented by general formula (u1)) In the above general formula (u1), R 1 is a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a halogenated alkyl group having 1 to 5 carbon atoms, and is preferably a hydrogen atom. In the above general formula (u1), Ar 01 is an aromatic group, and examples of the aromatic group include the same groups as the aromatic groups in the above-mentioned [Structural unit containing an aromatic group]. Ar 01 Of these, a phenyl group is preferred.

[0057] [Structural unit represented by general formula (u2)] In the above general formula (u2), R 2 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a halogenated alkyl group having 1 to 5 carbon atoms, preferably an alkyl group having 1 to 5 carbon atoms, and more preferably a methyl group. In the above general formula (u2), Ra 01is an alkyl group having 1 to 10 carbon atoms, preferably a linear or branched alkyl group having 1 to 5 carbon atoms, more preferably a methyl group, ethyl group, propyl group, isopropyl group, n-butyl group, isobutyl group, tert-butyl group, pentyl group, isopentyl group, or neopentyl group, and further preferably a methyl group.

[0058] [Terminal structure represented by general formula (e1)] In the above general formula (e1), R 1 and R 2 are R in general formula (u1), 1 and R in general formula (u2) 2 is equivalent to. Ra in the above general formula (e1) 01 is Ra in the above general formula (u2). 01 is equivalent to. Ar in the above general formula (e1) 01 represents Ar in the above general formula (u1). 01 is equivalent to.

[0059] L in the above general formula (e1) 01 is a divalent linking group, and is preferably an alkylene group having 1 to 10 carbon atoms. Specific examples of the alkylene group having 1 to 10 carbon atoms include linear alkylene groups such as a methylene group [-CH2-], an ethylene group [-(CH2)2-], a trimethylene group [-(CH2)3-], a tetramethylene group [-(CH2)4-], and a pentamethylene group [-(CH2)5-]; and alkylmethylene groups such as -CH(CH3)-, -CH(CH2CH3)-, -C(CH3)2-, -C(CH3)(CH2CH3)-, -C(CH3)(CH2CH2CH3)-, and -C(CH2CH3)2-. Examples of branched alkylene groups include alkyl ethylene groups such as -CH(CH3)CH2-, -CH(CH3)CH(CH3)-, -C(CH3)2CH2-, -CH(CH2CH3)CH2-, and -C(CH2CH3)2-CH2-; alkyl trimethylene groups such as -CH(CH3)CH2CH2- and -CH2CH(CH3)CH2-; and alkyl tetramethylene groups such as -CH(CH3)CH2CH2CH2- and -CH2CH(CH3)CH2CH2-. L in the above general formula (e1) 01 Among the above, is preferably a linear alkylene group having 1 to 10 carbon atoms, more preferably a linear alkylene group having 1 to 5 carbon atoms, and even more preferably a linear alkylene group having 2 to 5 carbon atoms.

[0060] In the block copolymer A, the ratio (Mn3 / Mn1) of the number average molecular weight (Mn1) of the polymer constituting the 1a block to the number average molecular weight (Mn3) of the polymer constituting the 3a block is preferably 0.05 to 1. From the viewpoint of easily obtaining a good process margin, the above ratio is more preferably 0.8 to 1, and further preferably 0.9 to 1. Furthermore, from the viewpoint of maintaining thermal mobility and suppressing defects, the above ratio may be, for example, 0.05 to 0.35, or 0.07 to 0.35.

[0061] Here, "defect" refers to all defects that can be detected when observing a pattern from directly above, including defects caused by foreign matter or deposits on the pattern surface, defects related to the pattern shape such as bridges between patterns and filled holes in patterns, and dislocation defects specific to directed self-assembly (DSA) lithography.

[0062] Specifically, Mn1 is preferably from 10,000 to 100,000, more preferably from 15,000 to 50,000, and even more preferably from 18,000 to 40,000. When Mn1 is within the above preferred range, the process margin is more likely to be improved and the occurrence of defects is more likely to be suppressed.

[0063] Specifically, Mn3 is preferably 1200 to 100000. From the viewpoint of easily obtaining a good process margin, Mn3 is more preferably 10000 to 50000, and further preferably 18000 to 40000. From the viewpoint of maintaining thermal mobility and suppressing defects, Mn3 may be, for example, 1500 to 11000, or 1800 to 10500.

[0064] The number average molecular weight (Mn1) of the block copolymer A and the number average molecular weight (Mn2) and Mn3 of the polymer constituting the 2a block can be calculated, for example, by the following method. For example, when block copolymer A has a 1a block (PS) made of polystyrene, a 2a block (PMMA) made of polymethyl methacrylate, and a 3a block (PS') made of polystyrene, and is a triblock copolymer (PS-b-PMMA-b-PS') in which the molecular weights of the 1a block and the 3a block are different, and PS' is bonded to a side chain of PMMA, it can be separated into PS-b-PMMA and PS' by hydrolysis. The Mn3 of the polymer PS' constituting the 3a block can be calculated by size exclusion chromatography. The number average molecular weight (Mn12) of a block copolymer having a 1a block and a 2a block can also be calculated. For a block copolymer having a 1a block and a 2a block, 1 Since the ratio of the polymer constituting the 1a block to the polymer constituting the 2a block in the block copolymer can be calculated by H-NMR, Mn1 and Mn2 can be calculated from the above Mn12. In addition, the number average molecular weight (Mn) of the block copolymer A and 1 If the structural units of the polymer constituting each block are known by H-NMR, Mn1, Mn2, and Mn3 can also be calculated from the relationship of L0.

[0065] The number average molecular weight (Mn) of the block copolymer A is preferably 20,000-200,000, more preferably 30,000-150,000, and further preferably 40,000-100,000. When the number average molecular weight (Mn) of the block copolymer A is within the above preferred range, the process margin is more likely to be improved and the occurrence of defects is more likely to be suppressed.

[0066] The dispersity (Mw / Mn) of the block copolymer A is preferably from 1.0 to 3.0, more preferably from 1.0 to 1.5, and even more preferably from 1.0 to 1.3.

[0067] In the block copolymer A, the ratio of the total mass of the 1a block and the 3a block to the mass of the 2a block (1a block and 3a block:2a block) is preferably 25:75 to 75:25, more preferably 30:70 to 70:30, and even more preferably 40:60 to 60:40. When the ratio is within the above preferred range, the phase-separated structure forming resin composition of the present embodiment is more likely to produce a phase-separated structure having a lamellar shape oriented in a direction perpendicular to the surface of the support, and the process margin during the formation of the structure is improved and the occurrence of defects is more suppressed. In this specification, the above ratio is 1 Calculated by H-NMR.

[0068] L0 of the block copolymer A is not particularly limited, and is, for example, from 10 nm to 60 nm, or from 10 nm to 40 nm. In this specification, L0 of the block copolymer is obtained by the evaluation method described in the examples below.

[0069] (Production method of block copolymer A) The block copolymer A can be produced by a known method. For example, block copolymer a can be obtained by living polymerization of a monomer that derives a constituent unit of the polymer constituting block 1a, a monomer that derives a constituent unit of the polymer constituting block 2a, and a monomer that derives a constituent unit of the polymer constituting block 3a. On the other hand, for example, when styrene and methyl methacrylate are used as monomers, the polymer may be produced by a production method including the steps (step A and step B) shown below. Step A: A step of polymerizing styrene and methyl methacrylate to obtain a block copolymer (PS-b-PMMA) Step B: A step of subjecting the block copolymer (PS-b-PMMA) obtained in step A to an ester exchange reaction with polystyrene having a hydroxyl group at the end of the main chain.

[0070] Process A: The polymerization of styrene and methyl methacrylate is preferably living polymerization because it can easily obtain a block copolymer (PS-b-PMMA). Preferred living polymerization methods include living anionic polymerization and living radical polymerization, and living anionic polymerization is particularly preferred because it can more narrowly disperse the polymer.

[0071] Process B: An example of the polystyrene having a hydroxy group at the main chain end in step B is a compound represented by the following formula (PS-OH).

[0072] [ka]

[0073] Step B may be carried out in the presence of a base catalyst. Specific examples of the base catalyst include 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD).

[0074] The reaction temperature in step B is preferably 50 to 200°C, more preferably 80 to 180°C. The reaction time in step B is preferably 10 to 300 hours.

[0075] <Block copolymer B> Block copolymer B is a block copolymer in which a 1b block and a 2b block are bonded together. The structural units of the polymer constituting the 1b block have the same structure as the structural units of the polymer constituting the 1a block of block copolymer A, and the structural units of the polymer constituting the 2b block have the same structure as the structural units of the polymer constituting the 2a block of block copolymer A.

[0076] The block copolymer B is preferably a diblock copolymer having no blocks other than the 1b block and the 2b block.

[0077] The number average molecular weight (Mn) of the block copolymer B is preferably 10,000 to 200,000, more preferably 20,000 to 100,000, and even more preferably 30,000 to 80,000, from the viewpoints of easily obtaining a good process margin and easily suppressing the occurrence of defects.

[0078] In the block copolymer B, the ratio of the mass of the 1b block to the mass of the 2b block (1b block:2b block) is preferably 25:75 to 75:25, more preferably 30:70 to 70:30, and even more preferably 40:60 to 60:40. When the ratio is within the above preferred range, the phase-separated structure forming resin composition of the present embodiment is likely to produce a lamellar phase-separated structure oriented in a direction perpendicular to the support surface. In addition, the process margin when forming the structure is further improved, and the occurrence of defects can be further suppressed. In this specification, the above ratio is 1 Calculated by H-NMR.

[0079] L0 of the block copolymer B is not particularly limited, and is, for example, from 10 nm to 60 nm, or from 10 nm to 40 nm.

[0080] L0 of block copolymer A (L0 A ) for block copolymer B (L0 B ) ratio (L0 B / L0 A ) is 0.70 to 1.20, preferably 0.80 to 1.10, and more preferably 0.90 to 1.00, since a good process margin is easily obtained.

[0081] The ratio of the mass of block copolymer A to the mass of block copolymer B (A:B) is preferably 99:1 to 50:50, more preferably 90:10 to 60:40, and further preferably 80:20 to 70:30, since a good process margin is easily obtained.

[0082] <Organic solvent components> The phase-separated structure-forming resin composition preferably contains an organic solvent. The organic solvent component may be any organic solvent capable of dissolving each component to be used and forming a homogeneous solution. Any organic solvent selected from organic solvents conventionally known as a solvent for compositions mainly composed of a resin may be used.

[0083] Examples of the organic solvent component include lactones such as γ-butyrolactone; ketones such as acetone, methyl ethyl ketone, cyclohexanone, methyl-n-pentyl ketone, methyl isopentyl ketone, and 2-heptanone; polyhydric alcohols such as ethylene glycol, diethylene glycol, propylene glycol, and dipropylene glycol; compounds having an ester bond such as ethylene glycol monoacetate, diethylene glycol monoacetate, propylene glycol monoacetate, and dipropylene glycol monoacetate; monoalkyl ethers such as monomethyl ether, monoethyl ether, monopropyl ether, and monobutyl ether of the polyhydric alcohols or the compounds having an ester bond, or monophenyl ethers having an ether bond. Examples of suitable organic solvents include derivatives of polyhydric alcohols such as compounds having the formula (among which, propylene glycol monomethyl ether acetate (PGMEA) and propylene glycol monomethyl ether (PGME) are preferred)]; cyclic ethers such as dioxane; esters such as methyl lactate, ethyl lactate (EL), methyl acetate, ethyl acetate, butyl acetate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, and ethyl ethoxypropionate; and aromatic organic solvents such as anisole, ethyl benzyl ether, cresyl methyl ether, diphenyl ether, dibenzyl ether, phenetole, butyl phenyl ether, ethylbenzene, diethylbenzene, pentylbenzene, isopropylbenzene, toluene, xylene, cymene, and mesitylene. The organic solvent component may be used alone or in a mixture of two or more kinds. Among them, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), cyclohexanone, and ethyl lactate (EL) are preferred.

[0084] A mixed solvent obtained by mixing PGMEA with a polar solvent is also preferred. The mass ratio (PGMEA:polar solvent) may be appropriately determined in consideration of the compatibility between PGMEA and the polar solvent, and is preferably 1:9 to 9:1, and more preferably 2:8 to 8:2. For example, when EL is blended as the polar solvent, the mass ratio of PGMEA:EL is preferably 1:9 to 9:1, more preferably 2:8 to 8:2. When PGME is blended as the polar solvent, the mass ratio of PGMEA:PGME is preferably 1:9 to 9:1, more preferably 2:8 to 8:2, and even more preferably 3:7 to 7:3. When PGME and cyclohexanone are blended as the polar solvent, the mass ratio of PGMEA:(PGME+cyclohexanone) is preferably 1:9 to 9:1, more preferably 2:8 to 8:2, and even more preferably 3:7 to 7:3.

[0085] In addition, as the organic solvent component in the phase-separated structure forming resin composition, a mixed solvent of PGMEA or EL, or the above-mentioned mixed solvent of PGMEA and a polar solvent, and γ-butyrolactone is also preferable. In this case, the mixing ratio of the former to the latter is preferably 70:30 to 95:5 by mass. The organic solvent component contained in the resin composition for forming a phase-separated structure is not particularly limited, and is appropriately set at a coatable concentration according to the coating film thickness, and is generally used so that the solid content concentration is within the range of 0.2 to 70 mass %, preferably 0.2 to 50 mass %.

[0086] <Optional ingredients> The phase-separated structure-forming resin composition may contain any optional components other than the above-mentioned block copolymer A, block copolymer B, and organic solvent component. Optional components include other resins, surfactants, dissolution inhibitors, plasticizers, stabilizers, colorants, antihalation agents, dyes, sensitizers, base multipliers, basic compounds, and the like.

[0087] <Method for producing structure including phase-separated structure> The method for producing a structure containing a phase-separated structure includes a step of forming a layer made of a neutralized film on a support (hereinafter referred to as "step (i)"), a step of applying the above-mentioned resin composition for forming a phase-separated structure onto the layer made of the neutralized film to form a layer containing block copolymer A and block copolymer B (hereinafter referred to as "step (ii)"), and a step of phase-separating the layer containing block copolymer A and block copolymer B (hereinafter referred to as "step (iii)"). Hereinafter, a method for producing such a structure containing a phase-separated structure will be specifically described with reference to Fig. 1. However, the present invention is not limited to this.

[0088] FIG. 1 shows an embodiment of a method for producing a structure containing a phase-separated structure. In the embodiment shown in FIG. 1, first, a base agent is applied onto a support 1 to form a layer 2 made of a neutralized film (FIG. 1(I); step (i)). Next, the above-mentioned resin composition for forming a phase-separated structure is applied onto the layer 2 made of the neutralized film to form a layer (BCP layer) 3 containing the block copolymer A and the block copolymer B (Figure 1 (II); this is step (ii)). Next, an annealing treatment is performed by heating, so that the BCP layer 3 is separated into a phase 3a and a phase 3b (FIG. 1(III); step (iii)). According to the manufacturing method of this embodiment, that is, the manufacturing method including steps (i) to (iii), a structure 3' including a phase-separated structure is produced on the layer 2 made of a neutral film.

[0089] <Process (i)> In step (i), a layer 2 made of a neutralized film is formed on a support 1 . In the embodiment shown in FIG. 1, first, a base agent is applied onto a support 1 to form a layer 2 made of a neutral film. By providing the layer 2 made of a neutral film on the support 1, the hydrophilic / hydrophobic balance between the surface of the support 1 and the layer (BCP layer) 3 containing a block copolymer can be achieved.

[0090] The type of the support 1 is not particularly limited as long as the resin composition can be applied onto the surface. For example, a substrate made of an inorganic material such as metal (silicon, copper, chromium, iron, aluminum, etc.), glass, titanium oxide, silica, mica, etc.; a substrate made of an oxide such as SiO2; a substrate made of a nitride such as SiN; a substrate made of an oxynitride such as SiON; a substrate made of an organic material such as acrylic, polystyrene, cellulose, cellulose acetate, phenol resin, etc. can be mentioned. Among these, a metal substrate is preferable, and for example, a lamellar structure is easily formed on a silicon substrate (Si substrate) or a copper substrate (Cu substrate). Among these, a Si substrate is particularly preferable. The size and shape of the support 1 are not particularly limited. The support 1 does not necessarily have to have a smooth surface, and substrates of various shapes can be appropriately selected. For example, substrates having a curved surface, flat plates with an uneven surface, and substrates having a flaky shape can be mentioned.

[0091] The surface of the support 1 may be provided with an inorganic and / or organic film. Examples of inorganic films include inorganic anti-reflective coatings (inorganic BARCs). Examples of organic films include organic anti-reflective coatings (organic BARCs). The inorganic film can be formed, for example, by applying an inorganic anti-reflective coating composition such as a silicon-based material onto a support and baking the composition. The organic film can be formed, for example, by applying an organic film-forming material, which is a resin component that constitutes the film, dissolved in an organic solvent, onto a substrate using a spinner or the like, and baking the material under heating conditions of preferably 200 to 300° C., preferably 30 to 300 seconds, more preferably 60 to 180 seconds. This organic film-forming material does not necessarily need to be sensitive to light or electron beams, unlike a resist film, and may or may not have sensitivity. Specifically, resists and resins that are commonly used in the manufacture of semiconductor elements and liquid crystal display elements can be used. In addition, in order to transfer the pattern of the phase separation structure to form an organic film pattern, the organic film forming material is preferably a material capable of forming an organic film that can be etched, particularly dry etched. In particular, it is preferable that the material be capable of forming an organic film that can be etched, such as oxygen plasma etching. Such an organic film forming material may be a material that has been used to form an organic film such as organic BARC. For example, the ARC series manufactured by Nissan Chemical Industries, Ltd., the AR series manufactured by Rohm and Haas, and the SWK series manufactured by Tokyo Ohka Kogyo Co., Ltd. can be mentioned.

[0092] As the undercoat agent, a resin composition can be used. The resin composition for the undercoat agent can be appropriately selected from among conventionally known resin compositions used for forming thin films, depending on the type of block constituting the block copolymer. The resin composition for the undercoat agent may be, for example, a thermally polymerizable resin composition, or may be a photosensitive resin composition such as a positive resist composition or a negative resist composition. In addition, a compound may be used as a surface treatment agent, and a non-polymerizable film formed by applying the compound may be used as a neutralized film. For example, a siloxane-based organic monomolecular film formed using phenethyltrichlorosilane, octadecyltrichlorosilane, hexamethyldisilazane, or the like as a surface treatment agent may also be suitably used as a neutralized film.

[0093] As the resin composition for the primer, it is preferable to use, for example, a composition containing a resin having both styrene and methyl methacrylate as constituent units, or a compound or composition containing both a moiety having high affinity for styrene, such as an aromatic ring, and a moiety having high affinity for methyl methacrylate (such as a highly polar functional group). Examples of resins having both styrene and methyl methacrylate as constituent units include random copolymers of styrene and methyl methacrylate, and alternating polymers of styrene and methyl methacrylate (polymers in which each monomer is copolymerized alternately). In addition, as a composition containing both a site having a high affinity for styrene and a site having a high affinity for methyl methacrylate, for example, there is a composition containing a resin obtained by polymerizing at least a monomer having an aromatic ring and a monomer having a functional group with high polarity. Examples of the monomer having an aromatic ring include monomers having aryl groups in which one hydrogen atom has been removed from an aromatic hydrocarbon ring, such as a phenyl group, a biphenyl group, a fluorenyl group, a naphthyl group, an anthryl group, or a phenanthryl group, or monomers having heteroaryl groups in which a part of the carbon atoms constituting the ring of these groups is substituted with a heteroatom such as an oxygen atom, a sulfur atom, or a nitrogen atom. In addition, examples of the monomer having a functional group with high polarity include monomers having a trimethoxysilyl group, a trichlorosilyl group, an epoxy group, a glycidyl group, a carboxy group, a hydroxyl group, a cyano group, or a hydroxyalkyl group in which a part of the hydrogen atoms of an alkyl group is substituted with a hydroxyl group. Other examples of compounds that contain both a moiety with high affinity for styrene and a moiety with high affinity for methyl methacrylate include compounds that contain both an aryl group and a highly polar functional group, such as phenethyltrichlorosilane, and compounds that contain both an alkyl group and a highly polar functional group, such as alkylsilane compounds.

[0094] The resin composition for the base agent can be produced by dissolving the above-mentioned resin in a solvent. Such a solvent may be any solvent capable of dissolving each component used to form a homogeneous solution, and examples thereof include the same organic solvent components as those exemplified in the description of the resin composition for forming a phase-separated structure described above.

[0095] The method for applying the undercoat agent onto the support 1 to form the layer 2 made of a neutralized film is not particularly limited, and may be formed by a conventionally known method. For example, the undercoat agent is applied onto the support 1 by a conventionally known method such as spin coating or using a spinner to form a coating film, and then dried to form the layer 2 made of a neutral film. The coating film can be dried by any method capable of volatilizing the solvent contained in the undercoat agent, such as baking. In this case, the baking temperature is preferably 80 to 300° C., more preferably 180 to 270° C., and further preferably 220 to 250° C. The baking time is preferably 30 to 500 seconds, and more preferably 60 to 400 seconds. The thickness of the layer 2 made of the neutralized film after drying of the coating film is preferably about 10 to 100 nm, and more preferably about 40 to 90 nm.

[0096] The surface of the support 1 may be washed before forming the layer 2 made of a neutral film on the support 1. Washing the surface of the support 1 improves the coatability of the undercoat agent. The cleaning treatment may be carried out by any of the conventional methods known in the art, including, for example, oxygen plasma treatment, ozone oxidation treatment, acid-alkali treatment, and chemical modification treatment.

[0097] After forming the layer 2 made of the neutralized film, the layer 2 made of the neutralized film may be rinsed with a rinsing liquid such as a solvent, if necessary. The rinsing removes uncrosslinked portions and the like in the layer 2 made of the neutralized film, improving the affinity with at least one block constituting the block copolymer, and facilitating the formation of a phase-separated structure made of a lamellar structure oriented perpendicular to the surface of the support 1. The rinse liquid may be any liquid capable of dissolving the uncrosslinked portions, and solvents such as propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), ethyl lactate (EL), or commercially available thinner liquids may be used. After the cleaning, post-baking may be performed to volatilize the rinsing liquid. The temperature condition for this post-baking is preferably 80 to 300°C, more preferably 100 to 270°C, and further preferably 120 to 250°C. The baking time is preferably 30 to 500 seconds, and more preferably 60 to 240 seconds. The thickness of the undercoat agent layer 2 after such post-baking is preferably about 1 to 10 nm, and more preferably about 2 to 7 nm.

[0098] <Process (ii)> In the step (ii), a resin composition for forming a phase-separated structure is then applied onto the layer 2 made of the neutralized film to form a layer (BCP layer) 3 containing the block copolymer A and the block copolymer B. The method for forming the BCP layer 3 on the layer 2 made of a neutralized film is not particularly limited, and examples thereof include a method in which the resin composition for forming a phase-separated structure of the above-mentioned embodiment is applied to the layer 2 made of a neutralized film by a conventionally known method such as spin coating or using a spinner to form a coating film, and then dried.

[0099] The thickness of the BCP layer 3 need only be sufficient for phase separation to occur, and taking into consideration the type of support 1, the structural period size of the phase-separated structure formed, the uniformity of the nanostructure, etc., the thickness is preferably 20 to 100 nm, and more preferably 30 to 80 nm. For example, when the support 1 is a Si substrate, the thickness of the BCP layer 3 is adjusted to preferably 10 to 100 nm, more preferably 30 to 80 nm.

[0100] <Step (iii)> In the step (iii), the BCP layer 3 formed on the layer 2 made of the neutralized film is subjected to phase separation. By heating the support 1 after step (ii) to perform an annealing treatment, a structure 3' including a phase-separated structure separated into a phase 3a and a phase 3b is produced on the layer 2 made of a neutral film. In a subsequent step, the phases are selectively removed to expose at least a part of the surface of the layer 2 made of a neutral film. The annealing temperature is preferably equal to or higher than the glass transition temperature of the block copolymer used and lower than the thermal decomposition temperature. For example, in the case of a polystyrene-polymethyl methacrylate (PS-PMMA) block copolymer (weight average molecular weight: 5,000 to 100,000), the annealing temperature is preferably 180 to 270°C, more preferably 200 to 270°C, and even more preferably 220 to 260°C. The heating time is preferably 1 minute to 1 hour, more preferably 2 to 45 minutes, and even more preferably 5 to 30 minutes. Moreover, the annealing process is preferably carried out in a gas with low reactivity, such as nitrogen.

[0101] The method for producing a structure including a phase-separated structure according to the embodiment described above has a good process margin because the resin composition for forming a phase-separated structure according to the embodiment described above is used.

[0102] In addition, according to the structure including the phase-separated structure of this embodiment, it is possible to produce a support having nanostructures on the surface of the support, the position and orientation of which can be designed more freely. For example, according to the method for producing a structure including a phase-separated structure of the present embodiment, the structure formed is likely to have a phase-separated structure consisting of a lamellar structure.

[0103] <Optional process> The method for producing a structure containing a phase-separated structure is not limited to the above-mentioned embodiment, and may include steps (optional steps) other than steps (i) to (iii).

[0104] Such optional steps include a step of selectively removing a phase of at least one type of block among the blocks constituting the block copolymer in the BCP layer 3 (hereinafter referred to as “step (iv)”), a guide pattern formation step, and the like.

[0105] Regarding step (iv) In step (iv), a phase consisting of at least one type of block among the blocks constituting the block copolymer in the BCP layer 3 formed on the layer 22 consisting of the neutral film is selectively removed, thereby forming a fine pattern (polymer nanostructure).

[0106] Methods for selectively removing the phase consisting of blocks include a method of subjecting the BCP layer to oxygen plasma treatment, a method of subjecting the BCP layer to hydrogen plasma treatment, and the like. For example, by subjecting a BCP layer containing the block copolymer to phase separation and then subjecting the BCP layer to oxygen plasma treatment, hydrogen plasma treatment, or the like, the phase consisting of the 1a and 3a blocks is not selectively removed, but the phase consisting of the 2a block is selectively removed.

[0107] FIG. 2 shows an example embodiment of step (iv). In the embodiment shown in Figure 2, the structure 3' produced on the support 1 in step (iii) is subjected to an oxygen plasma treatment, whereby the phase 3a is selectively removed and a pattern (polymer nanostructure) consisting of spaced phases 3b is formed.

[0108] The support 1 on which a pattern has been formed by phase separation of the BCP layer 3 made of the block copolymer as described above can be used as is, but the shape of the pattern (polymer nanostructure) on the support 1 can also be changed by further heating. The heating temperature is preferably equal to or higher than the glass transition temperature of the block copolymer used and lower than its thermal decomposition temperature, and is preferably carried out in a gas with low reactivity such as nitrogen.

[0109] Guide pattern formation process The method for producing a structure containing a phase-separated structure may include a step of providing a guide pattern on the layer made of a neutral film (guide pattern forming step), which makes it possible to control the arrangement of the phase-separated structure. For example, even if a block copolymer forms a random fingerprint-like phase separation structure when no guide pattern is provided, a phase separation structure oriented along the grooves can be obtained by providing a groove structure of a resist film on a layer made of a neutralization film. In addition, when the surface of the guide pattern has affinity with any of the blocks constituting the block copolymer, a phase separation structure consisting of a lamellar structure oriented perpendicular to the support surface can be easily formed.

[0110] The guide pattern can be formed using, for example, a resist composition. The resist composition for forming the guide pattern can be appropriately selected from resist compositions generally used for forming resist patterns and their modified products, and can be used as a resist composition having affinity with any of the blocks constituting the block copolymer. The resist composition can be either a positive resist composition for forming a positive pattern in which the exposed portion of the resist film is dissolved and removed, or a negative resist composition for forming a negative pattern in which the unexposed portion of the resist film is dissolved and removed, but is preferably a negative resist composition. For example, the negative resist composition is preferably a resist composition containing an acid generator and a base material component whose solubility in a developer containing an organic solvent is reduced by the action of an acid, and the base material component contains a resin component having a structural unit that is decomposed by the action of an acid to increase polarity. After the phase-separated structure forming resin composition is poured onto the layer made of the neutralized film on which the guide pattern is formed, an annealing treatment is performed to cause phase separation. Therefore, as the resist composition for forming the guide pattern, a resist composition capable of forming a resist film having excellent solvent resistance and heat resistance is preferable. EXAMPLES

[0111] Based on the examples, the present invention will be described in more detail, but the present invention is not limited by these examples.

[0112] The block copolymers A and B used in the examples and comparative examples will be described below. The number average molecular weight (Mn), the copolymer composition ratio (PS:PMMA), and L0 of the block copolymers A and B, and the ratio (Mn3 / Mn1) of the number average molecular weight (Mn1) of the polymer constituting the first a-block and the number average molecular weight (Mn3) of the polymer constituting the third a-block of the block copolymer A are shown in Table 1.

[0113] (Block copolymer A) A1: A triblock copolymer (PS-b-PMMA-b-PS) having a first a-block (PS) made of polystyrene, a second a-block (PMMA) made of polymethyl methacrylate, and a third a-block (PS) made of polystyrene, and the molecular weights of the first a-block and the third a-block are the same. A2: A triblock copolymer (PS-b-PMMA-b-PS') having a first a-block (PS) made of polystyrene, a second a-block (PMMA) made of polymethyl methacrylate, and a third a-block (PS') made of polystyrene, and the molecular weights of the first a-block and the third a-block are different, and is obtained in the following synthesis example. (Block copolymer B) B1 to B4: A diblock copolymer (PS-b-PMMA) having a first b-block (PS) made of polystyrene and a second b-block (PMMA) made of polymethyl methacrylate.

[0114] <Synthesis example of A2> A stirrer, 500 mg of PS-b-PMMA, and 250 mg of a compound represented by the following formula (PS-OH) were added to a flask (30 mL) equipped with a greaseless valve. The flask was heated to 100° C. in an aluminum bath. The contents of the flask were dried overnight under vacuum at the same temperature. After drying, 5 mg (0.0357 mmol) of TBD (1,5,7-triazabicyclo[4.4.0]dec-5-ene) dissolved in 5 mL of toluene was added to the flask. Next, the flask was heated to 150° C. in an aluminum bath, and the contents of the flask were stirred at the same temperature. After stirring, the temperature in the flask was returned to room temperature, and about 5 mg of benzoic acid was added to the flask. Next, the product was reprecipitated with MeOH at room temperature. Next, the precipitate formed by reprecipitation was vacuum dried. The sample (only 300 mg) was dispersed in cyclohexane, stirred at 75° C. for 15 minutes, and centrifuged to remove the solvent. This process was performed three times. After the third centrifugation, reprecipitation and vacuum drying were performed to obtain A2 (PS-b-PMMA-b-PS').

[0115] [ka]

[0116] [ka]

[0117] [Table 1]

[0118] <Preparation of resin composition for forming phase-separated structure> Block copolymer A and block copolymer B having the types and ratios shown in Tables 2 and 3 were dissolved in propylene glycol monomethyl ether acetate (PGMEA) to prepare a phase-separated structure-forming resin composition (solid content concentration: 1.3% by mass).

[0119] [Evaluation of the period of the structure (L0)] A resin composition for forming a neutral film, which is a PGMEA solution of styrene / methyl methacrylate / 2-hydroxyethyl methacrylate copolymer (copolymerization ratio: styrene / methyl methacrylate / 2-hydroxyethyl methacrylate = 82 / 12 / 6 (mass%)) with a concentration of 2 mass%, was applied onto a 12-inch silicon wafer using a spinner. The applied film was baked at 250°C for 300 seconds to form a layer of a neutral film with a thickness of 60 nm on the silicon wafer. Next, the neutralized film was removed from the silicon wafer using a solvent (OK73 thinner (Tokyo Ohka Kogyo Co., Ltd.)). A 1.3% by mass solution of block copolymer A or block copolymer B in PGMEA was spin-coated onto the layer made of the neutralized film, and then soft-baked at 90°C for 60 seconds to form a block copolymer layer with a thickness of 35 nm. The silicon wafer was annealed by heating at 250°C for 30 minutes under a nitrogen gas flow to form a structure containing a phase separation structure. Then, a selective removal process of the blocks was performed to form a finger print pattern. Images of the formed pattern were obtained using a Hitachi High-Technologies Corporation-manufactured length-measuring scanning electron microscope (CG6300 (Hitachi High-Technologies Corporation)). One hundred images obtained were analyzed using image analysis software (DSA-APPS (Hitachi High-Technologies Corporation)), and the average value of L0 was calculated based on the L0 values ​​calculated for the 100 images. The results are shown in Table 1 as "L0 (nm)".

[0120] [Evaluation of process margins] A resin composition for forming a polystyrenated film, which is a PGMEA solution of styrene / vinylbenzocyclobutene copolymer with a concentration of 0.4% by mass, was applied to a 12-inch silicon wafer having a silicon nitride film as an anti-reflective film using a spinner. The applied film was baked at 250°C for 300 seconds to form a layer of a polystyrenated film with a thickness of 8 nm on the silicon wafer. Then, an ArF photoresist for immersion exposure was applied onto the polystyrenated film to form a coating film, which was then baked at 90°C for 60 seconds. Next, the baked coating film was exposed to light using an ArF immersion exposure tool (ASML NXT1900i scanner, NA: 1.35, quadrupole, 0.87, 0.72), and then post-exposure bake was performed at 110° C. for 60 seconds. After development, a pattern of the polystyrenated film was formed by plasma etching using oxygen / nitrogen plasma, followed by resist stripping and post-baking at 100°C for 60 seconds. Then, a neutralized film-forming resin composition, which is a PGMEA solution of a styrene / methyl methacrylate / hydroxyethyl methacrylate copolymer with a concentration of 2% by mass, was applied onto the patterned polystyrenated film to form a coating film. The formed coating film was baked at 250°C for 300 seconds, rinsed with OK73 thinner, and post-baked at 100°C for 60 seconds to obtain an evaluation guide substrate having a guide pattern in which the polystyrenated film and the neutralized film were repeated. The obtained guide substrate was divided into small pieces for each repeating pattern and used for evaluation.

[0121] The resin composition for refining a phase-separated structure was applied to a guide substrate to form a coating film, which was then baked at 90° C. for 60 seconds and then annealed at 250° C. for 5 hours to form a phase-separated pattern. After that, the surface of the formed phase separation pattern was made uneven by oxygen plasma ashing. Next, platinum was vapor-deposited onto the surface of the phase separation pattern. The surface of the platinum-deposited phase separation pattern was observed with a scanning electron microscope (SEM, SU8000 (Hitachi High-Technologies Corporation)). The number of cells without defects was confirmed using a guide with a guide pitch (X direction, width of one period in the guide pattern) and guide dimension (Y direction, width of the polystyrene film in the guide pattern). The greater the number of cells without defects, the more likely it is that one block copolymer can be used for multiple pitches. The results are shown in Tables 2 and 3 as "process margins."

[0122] [Table 2]

[0123] [Table 3]

[0124] As shown in Tables 1 and 2, the composition contains a predetermined block copolymer A and a block copolymer B, and L0 B / L0 A It is clear that the phase-separated structure-forming resin compositions of the Examples, in which the value is 0.70 to 1.20, have better process margins than the phase-separated structure-forming resin compositions of the Comparative Examples.

Claims

1. A phase-separated structure-forming resin composition containing a block copolymer A and a block copolymer B, The block copolymer A is a block copolymer in which a 1a block, a 2a block, and a 3a block are bonded together, The block copolymer B is a block copolymer in which a 1b block and a 2b block are bonded together, a structural unit of the polymer constituting the 1a block, a structural unit of the polymer constituting the 3a block, and a structural unit of the polymer constituting the 1b block have the same structure, a structural unit of a polymer constituting the 2 a block and a structural unit of a polymer constituting the 2 b block have the same structure, L0 of the block copolymer A (L0 A ) to L0 (L0 B ) ratio (L0 B / L0 A ) is 0.70 to 1.

20.

2. 2. The phase-separated structure forming resin composition according to claim 1, wherein a ratio (A:B) of a mass of the block copolymer A to a mass of the block copolymer B is 99:1 to 50:

50.

3. the 1a block, the 3a block, and the 1b block are each composed of a polymer having a structural unit containing an aromatic group, 3. The phase-separated structure-forming resin composition according to claim 1, wherein the second a block and the second b block are made of a polymer having a structural unit derived from an (α-substituted) acrylic acid ester.

4. forming a layer of a neutralized film on a support; A step of applying the resin composition for forming a phase-separated structure according to claim 1 or 2 onto the layer made of the neutralized film to form a layer containing the block copolymer A and the block copolymer B; and causing phase separation of a layer containing the block copolymer A and a layer containing the block copolymer B.

Citation Information

Patent Citations

  • Pattern formation method and mold

    JP2008036491A

Cited By

  • Resin composition for forming phase separation structure, and method for producing laminate

    WO2026197375A1